Tool life of ceramic wedges during precise turning of tungsten - Legutko Stanislaw; Winiarski Piotr; Chwalczuk Tadeusz; Marcincinova-Novakova Ludmila; Zak Krzysztof (MATEC Web of Conferences, 2017)
Properties, application and machinability of tungsten and its alloys have been demonstrated. The comparison of the tool life and wear of the wedges made of SiAlON and whisker ceramics during the precise turning at different cutting parameters have been presented. The CNC lathe DMG CTX 310 Ecoline and tungsten of 99.7 % purity were used during the experiments. Only the wedge of whisker ceramics has proved to be sufficiently suitable and only for relatively low cutting speeds.